Time-varying association between severe respiratory syncytial virus infections and subsequent severe asthma and wheeze and influences of age at the infection - Wang, X; Li, Y; Nair, H; Campbell, H; Pollard, AJ (Oxford University Press, 2021)
Background Early-life severe respiratory syncytial virus (RSV) infection has been associated with subsequent risk of asthma and recurrent wheeze. However, changes in the association over time and the interaction effect of the age at first RSV infection are less well understood. We aimed to assess the time-varying association between RSV and subsequent asthma and wheeze admission and explore how the association was affected by the age at RSV infection. Methods We retrospectively followed up a cohort of 23 365 children for a median of 6.9 years using Scottish health databases. Children who were born between 2001 and 2013 and had RSV-associated respiratory tract infection (RTI) admissions under 2 years were in the exposed group; those with unintentional accident admissions under 2 years comprised the control group. The Cox proportional-hazards model was used to report adjusted hazard ratios (HRs) of RSV admissions on subsequent asthma and wheeze admissions. We did subgroup analyses by follow-up years. We also explored how this association was affected by the age at first RSV admission. Results The association was strongest in the first 2 years of follow-up and decreased over time. The association persisted for 6 years in children whose first RSV-RTI admission occurred at 6–23 months of age, with an adjusted HR of 3.9 (95% confidence interval [CI], 3.1–4.9) for the first 2 years, 2.3 (95% CI, 1.6–3.2) for 2 to <4 years, and 1.9 (95% CI, 1.2–2.9) for 4 to <6 years of follow-up. In contrast, the association was only significant for the first 2 years after first RSV-RTI admissions occurring at 0–5 months. Conclusions We found a more persistent association for subsequent asthma and wheeze in children whose first severe RSV infection occurred at 6–23 months compared to those whose first severe RSV infection occurred at 0–6 months. This provides new evidence for further assessment of the association and RSV intervention programs.